2002
DOI: 10.1159/000049063
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Mac-1 and CD14 Expression on Monocytes and Serum Soluble CD14 Level during Push/Pull Hemodiafiltration

Abstract: Background/Aim: Employment of treated dialysate as replacement fluid raises concerns about exposure of patients to pyrogenic substances. This study was undertaken to evaluate the safety of treated dialysate as the replacement fluid for push/pull hemodiafiltration. Methods: In the present study, changes in the expressions of Mac-1 and CD14 on monocytes, which are upregulated by monocyte activation, were analyzed by flow cytometry, and the serum level of sCD14 which elevates by monocyte activation was measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Cell membrane CD14 is mostly found on the surface of monocytes and macrophages (Troelstra et al, 1997) and is involved in recognizing gram-negative bacteria, whereas CD18 is found on the neutrophil cell surface and is involved in cell migration toward a site of infection (Yagi et al, 2004). Increased expression of cell membrane CD14 is often used as an indicator of monocyte activation, as it occurs in response to lipopolysaccharide, which is a major component of the outer membrane of gram-negative bacteria (Kawabata et al, 2002). However, it is also associated with a response to physiological or psychological stress in rats, humans, and calves (Kawabata et al, 2002;Reber et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell membrane CD14 is mostly found on the surface of monocytes and macrophages (Troelstra et al, 1997) and is involved in recognizing gram-negative bacteria, whereas CD18 is found on the neutrophil cell surface and is involved in cell migration toward a site of infection (Yagi et al, 2004). Increased expression of cell membrane CD14 is often used as an indicator of monocyte activation, as it occurs in response to lipopolysaccharide, which is a major component of the outer membrane of gram-negative bacteria (Kawabata et al, 2002). However, it is also associated with a response to physiological or psychological stress in rats, humans, and calves (Kawabata et al, 2002;Reber et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of cell membrane CD14 is often used as an indicator of monocyte activation, as it occurs in response to lipopolysaccharide, which is a major component of the outer membrane of gram-negative bacteria (Kawabata et al, 2002). However, it is also associated with a response to physiological or psychological stress in rats, humans, and calves (Kawabata et al, 2002;Reber et al, 2008). Moreover, Reber et al (2008) found that calves that were not fed maternal colostrum had a greater cell surface density of CD14 than calves fed colostrum and concluded that this may be an indicator of stress.…”
Section: Discussionmentioning
confidence: 99%